THE ROLE OF INDUSTRIAL ENTERPRISES IN THE SOCIO-ECONOMIC LIFE OF THE POPULATION OF SURKHANDARYA REGION (FROM THE 20TH CENTURY TO THE FIRST QUARTER OF THE 21ST CENTURY) (Innovate Conferences, 2025)
This study examines the role of industrial enterprises in shaping the socio-economic life of the population in Surkhandarya Region from the 20th century to the first quarter of the 21st century. It explores the historical evolution of industry, from early Soviet industrialization to the modern post-independence era. The research highlights how industrial development influenced employment, urbanization, and living standards. Special attention is given to the transformation of production structures and labor relations. The study also analyzes the region’s industrial diversification and modernization policies after 1991. Statistical and comparative methods are used to assess economic growth and social welfare. Industrial enterprises are shown to be key drivers of regional economic stability. The paper discusses both positive impacts and environmental challenges of industrial expansion. In conclusion, it provides recommendations for sustainable industrial and social development in Surkhandarya Region.